FernGully. II The magical rescue - Robinson, Phil.; Young, Diana; CBS Fox Video; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. CBS Fox Video ; distributed by Twentieth Century Fox Home Entertainment, 2001)
All is well in FernGully until the day a group of humans comes in and captures three baby animals under Crysta's care.
Based on the stories of : FernGully by Diana Young.
Editor, Michael Cavanaugh ; original score, Nerida Tyson- Chew.
MPAA rating: G
VCD.
Keywords: Kidnapping -- Drama; Rain forests -- Drama; Feature films